2017
DOI: 10.1002/mnfr.201700118
|View full text |Cite
|
Sign up to set email alerts
|

Dietary advanced glycation end products modify gut microbial composition and partially increase colon permeability in rats

Abstract: Dietary AGEs detrimentally modulate gut microbial ecology and may partially increase colon permeability, which can adversely impact host health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(146 citation statements)
references
References 70 publications
5
138
1
2
Order By: Relevance
“…). Our research group recently showed that rats fed an AGE‐enriched diet produced via heat treatment of the AIN‐93G diet, the colon also showed no obvious inflammatory infiltration; however, this study demonstrated that dietary AGEs may increase colon permeability, which can adversely impact host health (Qu et al ., ). Therefore, although there was no significant inflammatory infiltration observed in the histological analysis of the colon and duodenum, the changes in inflammatory factor levels revealed damage to the colon and duodenum.…”
Section: Resultsmentioning
confidence: 97%
“…). Our research group recently showed that rats fed an AGE‐enriched diet produced via heat treatment of the AIN‐93G diet, the colon also showed no obvious inflammatory infiltration; however, this study demonstrated that dietary AGEs may increase colon permeability, which can adversely impact host health (Qu et al ., ). Therefore, although there was no significant inflammatory infiltration observed in the histological analysis of the colon and duodenum, the changes in inflammatory factor levels revealed damage to the colon and duodenum.…”
Section: Resultsmentioning
confidence: 97%
“…Dietary restriction of AGEs can alter the microbiota composition in humans [84], but at present we are not aware of interventions that have investigated whether AGE-induced changes in the microbiome lead to changes in markers of disease in humans. In rats, a diet high in AGEs led to reduced levels of strains associated with positive health effects, increased levels of species associated with detrimental health effects [82,85] as well as increased colon permeability [85], but there are rodent and in vitro studies where the results appear contradictory to this [82,[86][87][88]. Due to the heterogeneity and the multitude of AGEs that arise from heat treatment of processed foods, and their apparent contradictory effect, heat-treatment procedures that could have a potential detrimental effect on the gut microbiota warrant further investigation.…”
Section: Other Components Of the Western Diet That Influence Inflammamentioning
confidence: 99%
“…Показано, что у индивидов с нормальной почечной функцией примерно третья часть ПРМ выводятся с мочой, тогда как у пациентов с почечной недоста-точностью, например у тех, кто нуждается в гемодиа-лизе или перитонеальном диализе, ПРМ способны аккумулироваться в организме [58][59][60]. Оставшаяся часть потребляемых с пищей ПРМ перемещается в толстую кишку, где они взаимодействуют с ми-кробиотой кишечника, модулируя ее состав [61][62][63]. Из литературы известно, что некоторые ПРМ из группы продуктов Амороди, такие как фруктозели-зин, плохо абсорбируются в кишечнике, но способны утилизироваться определенными видами бактерий, населяющих кишечник человека [64].…”
Section: российский вестник перинатологии и педиатрии 2018; 63:(4) Runclassified
“…Однако уже сегодня понятно, что гликирование молочных белков может изменять их протеолиз [83,84]. Такие ПРМ, как КМЛ способны модулировать микробиоту кишечника [85,86]. У мла-денцев, получавших с молочным питанием повы-шенные уровни КМЛ, регистрировали повышенные уровни этого соединения в образцах плазмы и мочи [68,87].…”
Section: российский вестник перинатологии и педиатрии 2018; 63:(4) Runclassified